Lākhauṃ śiśu liphṭa māgirahechan : ʻCakrapāṇiʼ-kā sāmayika carcā, 1968-69-70 ; sampādaka Madanamaṇi Dīkshita - Cakrapāṇi (Madanamaṇi Dīkshita, 1981)
Satirical writings on the social and political conditions in Nepal; previously published in the Samīkshā, Nepali weekly.